Research methods in language teaching and learning a practical guide - Dikilitas, Kenan; Reynolds, Kate Mastruserio (Guides to research methods in language and linguistics, 2022)
"In the book, we begin with qualitative research narratives which have been written by researchers who published journal articles or Ph.D. theses on the key approaches to qualitative research. Their experiences during the development of the research plan, implementation, writing up, and dissemination are unique and can offer insightful stories that include not only background knowledge about the method, but also research learning opportunities. In chapter 1, 'Learning to Use a Qualitative Case Study Approach to Research Language Teachers' Self-Efficacy Beliefs' Mark Wyatt introduces case study methodology in which he investigated teacher self-efficacy beliefs. Having narrated how his initial interest in self-efficacy commenced, he provided methodological details about his research plan deriving from qualitative case study approach. Wyatt's chapter offers in-depth contextualized and procedural insights which can help others learn from his experiences and methodological interpretations he made while adopting case study"--Provided by publisher.